Differential T cell homing to colon vs. small intestine is imprinted by local CD11c+ APCs that determine homing receptors. Issue 6 (26th September 2017) - Dzutsev, Amiran; Hogg, Alison; Sui, Yongjun; Solaymani‐Mohammadi, Shahram; Yu, Huifeng; Frey, Blake; Wang, Yichuan; Berzofsky, Jay A.
Abstract : Colonic CD11c + antigen‐presenting cells imprint CD8 T cell homing back to the colon, and not the small intestine, dependent on differential retinoic‐acid levels inducing different homing receptors. Abstract : Mechanisms that imprint T cell homing to the small intestine have been well studied; however, those for homing to the colon are poorly understood. Recently, we found that these are distinct subcompartments of the gut mucosal immune system, which implies differential homing. Here, we show that colonic CD11c + APCs imprint CD8 + T cell preferential homing to the colon, in contrast to those from the small intestine that imprint CD8 + T cell homing to the small intestine, and that the differences are related to the variable ability of APCs to induce α4β7‐integrin and CCR9 expression on T cells. Colon APCs also expressed lower levels of retinoic acid–producing enzymes that are known to control the mucosal homing of T cells. These findings are the first to our knowledge to directly demonstrate that colon APCs imprint T cells to selectively home to the large bowel, which is critical for the design of successful T cell–based therapies and vaccines, such as colon cancer immunotherapy and HIV vaccines.